Particulate matter and risk of parkinson disease in a large prospective study of women - Palacios, Natalia (BioMed Central, 2014)
BACKGROUND: Exposure to air pollution has been implicated in a number of adverse health outcomes and the effect of particulate matter (PM) on the brain is beginning to be recognized. Yet, no prospective study has examined the association between PM and risk of Parkinson Disease. Thus, our goal was assess if exposure to particulate matter air pollution is related to risk of Parkinson’s disease (PD) in the Nurses’ Health Study (NHS), a large prospective cohort of women. METHODS: Cumulative average exposure to different size fractions of PM up to 2 years before the onset of PD, was estimated using a spatio-temporal model by linking each individual’s places of residence throughout the study with location-specific air pollution levels. We prospectively followed 115,767 women in the NHS, identified 508 incident PD cases and used multivariable Cox proportional hazards models to estimate the risk of PD associated with each size fraction of PM independently. RESULTS: In models adjusted for age in months, smoking, region, population density, caffeine and ibuprofen intake, we observed no statistically significant associations between exposure to air pollution and PD risk. The relative risk (RR) comparing the top quartile to the bottom quartile of PM exposure was 0.99 (95% Confidence Intervals (CI): 0.84,1.16) for PM(10) (≤10 microns in diameter), 1.08 (95% CI: 0.81, 1.45) for PM(2.5) (≤2.5 microns in diameter), and 0.92 (95% CI: 0.71, 1.19) for PM(10–2.5) (2.5 to 10 microns in diameter). CONCLUSIONS: In this study, we found no evidence that exposure to air pollution is a risk factor for PD.